Optimasi Parameter Tekanan Deposisi pada Penumbuhan Lapisan Tipis Polykristal Silikon dengan Metode Hot Wire Cell PECVD - Amiruddin Supu; Ida Usman; Mursal Mursal; Toto Winata; Sukirno Sukirno (Jurnal Matematika & Sains, 2005)
The Hot wire Cell PECVD method has been developed to grow the poly-Si thin films. The poly-Si thin films were grown on the 7059 corning glass at a filament temperature of 1800 oC. Silane (SiH4) gas 10% diluted in hydrogen (H2) gas was used as gas source. In the hot wire cell PECVD method, reactant gases were decomposed as a result of reaction with a heated filament placed above the substrate and paralel to the gas inlet. The characterization results exhibited that the poly-Si thin films could be grown at the pressure of 200 to 500 mTorr with a substrate temperature of 275 oC. The analysis of XRD result showed that preferential intensity was obtained at the crystal orientation of . The highest values of peak intensity (111 cps), grains size (minor axis 0.5 Âµm) and dark conductivity (0.60x10-5 Scm-1) were obtained at the deposition pressure of 300 mTorr with deposition rate of 2.2 nm/s.